A generic biokinetic model for Carbon-14 - Manger, R. P. (Radiation protection dosimetry, 2011)
The generic biokinetic model currently recommended by the International Commission on Radiological Protection (ICRP) for the treatment of systemic radiocarbon assumes uniform distribution of activity in tissues and a biological half-time of 40 d. This model is intended to generate cautiously high estimates of dose per unit intake of C-14 and, in fact, generally predicts a much higher effective dose than systemic models that have been developed on the basis of biokinetic studies of specific carbon compounds. The simplistic model formulation precludes its application as a bioassay model or adjustment to fit case-specific bioassay data. This paper proposes a new generic biokinetic model for systemic radiocarbon that is less conservative than the current ICRP model but maintains sufficient conservatism to overestimate the effective dose coefficients generated by most radiocarbon-compound-specific models. The proposed model includes two systemic pools with different biological half-times representing an initial systemic form of absorbed radiocarbon, a submodel describing the behaviour of labelled carbon dioxide produced in vivo, and three excretion pathways: breath, urine and faeces. Generic excretion rates along each path are based on multi-phase excretion curves observed in experimental studies of radiocarbons. The generic model structure is designed so that the user may adjust the level of dosimetric conservatism to fit the information at hand and may adjust parameter values for consistency with subject-specific or site-specific bioassay data.